2001
DOI: 10.1159/000047129
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Birth Weight and Placenta Weight

Abstract: With the goal to establish a model that relates birth weight to placenta weight, adjusted for the most documented predictors of birth weight, 300 live newborns were studied, all were products of single gestation. Inclusion criteria were newborns with gestational age of 37 weeks or older according to the date of last menstruation, whose mothers did not have diabetes mellitus, high blood pressure, pre-eclampsia, or eclampsia. The weight of the newborn was identified from the anthropometry data collected by previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
3
24
1
1
Order By: Relevance
“…The mean placental weight was found at 563.6±135.65 grs, and the mean of newborn weight was 3358±487.58 grs. Similarly, Sanin et al found that the average birth weight was 3369 ± 445 grs, and the average placenta weight was 537±96 grs (Sanin et al, 2001). Benirschke and Kaufmann reported the mean placenta weight at 38 weeks gestation as 470 grs without the cord and membrane; Petekkaya et al found the mean placental weight as 445.14±88 grs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The mean placental weight was found at 563.6±135.65 grs, and the mean of newborn weight was 3358±487.58 grs. Similarly, Sanin et al found that the average birth weight was 3369 ± 445 grs, and the average placenta weight was 537±96 grs (Sanin et al, 2001). Benirschke and Kaufmann reported the mean placenta weight at 38 weeks gestation as 470 grs without the cord and membrane; Petekkaya et al found the mean placental weight as 445.14±88 grs.…”
Section: Discussionmentioning
confidence: 83%
“…Alwasel et al(2010) reported that high maternal body mass index was associated with a high placental ratio (placental weight/birth weight) at birth. Sanin et al (2001) revealed that for each gram increase in placental weight, birth weight increased by 1.98 g.; placental weight has a nonlinear relation to the birth weight and is an important predictor of birth weight. Petekkaya et al (2011) reported that only the relationship between placental weight and newborn weight was found to be statistically significant (r=0.543, p<0.001); no statistically significant relationship was found among placental weight and the age of the mother, number of births, newborn gender and height.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger population size from Mexico (n: 300 live newborns) Sanin established a model to relate birth weight with placental weight [4]. Placental weight was found to be significantly related to birth weight.…”
Section: Methodsmentioning
confidence: 99%
“…This increase in placenta weight results in increased vascularity in the placental disc and giving a larger blood volume. [20] In the current study, there were significant differences between the blood volume and nucleated cell content taken from the first baby and those taken from the after coming ones. There were larger blood volume and higher cellular count among the first born babies compared to the second or more babies.…”
Section: Discussionmentioning
confidence: 46%